2021
DOI: 10.35334/be.v5i1.1681
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kinerja Simpang Empat Bersinyal Dengan Metode MKJI dan Sidra Intersection

Abstract: Pada lima tahun terakhir pertumbuhan pembangunan di sepanjang ruas jalan MT. Haryono mengalami pertumbuhan yang sangat pesat, mulai dari pembangunan property (perumahan dan ruko), pusat perbelanjaan, hingga menjamurnya usaha kuliner di sepanjang sisi ruas jalan, hal ini menyebabkan tingginya tarikan kendaraan menuju daerah tersebut. Adanya alih fungsi tata guna lahan di beberapa lokasi di Balikpapan menyebabkan tingginya bangkitan dan tarikan kendaraan pada daerah tersebut. Pada ruas jalan MT. Haryono terdapat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Makino et al [22] showed that some cities are using modern information and communication technologies to solve their urban traffic problems using intelligent transport systems (ITS), and some of these cities have had success with the installation of these systems. Akcelik and Associates Pty Ltd. created software called SIDRA Intersection signalized and unsignalized Intersection design and Research Aid is the abbreviation for this study [23]. SIDRA is renowned for having benefits over other software models when comparing the efficacy of various types of intersections.…”
Section: Original Researchmentioning
confidence: 99%
“…Makino et al [22] showed that some cities are using modern information and communication technologies to solve their urban traffic problems using intelligent transport systems (ITS), and some of these cities have had success with the installation of these systems. Akcelik and Associates Pty Ltd. created software called SIDRA Intersection signalized and unsignalized Intersection design and Research Aid is the abbreviation for this study [23]. SIDRA is renowned for having benefits over other software models when comparing the efficacy of various types of intersections.…”
Section: Original Researchmentioning
confidence: 99%